Implementasi E-Audit System Pada Proses Reviu Laporan Keuangan Uo Tni Ad Oleh Apip - Belle, Muharram; Sartika , Ika (Green Publisher Indonesia, 2025)
This research aims to determine the effectiveness of the implementation of the E-Audit System in the financial report review process conducted by the Government Internal Supervisory Apparatus (APIP). This study uses a qualitative method with data from the financial report review at UO TNI AD. ….which defines a business process as